Cash Waqf risk management and perpetuity restriction conundrum - Azrai Azaimi Ambrose, Azniza Hartini; Abdullah Asuhaimi, Fadhilah (Emerald Publishing Limited, 2021)
Purpose: The purpose of this paper is to comprehensively discuss the issue of risk vis-à-vis the perpetuity restriction principle inherent in waqf (Islamic endowment). Specifically, it attempts to consolidate the axioms in both conventional and Islamic finance, such as the risk-return trade-off and al-ghunm bi al-ghurm (liability accompanies gain), with the perpetual nature of waqf. Overall, this paper attempts to find a resolution to the dilemma of perpetuity restriction inherent in cash waqf against the natural occurrence of the risk.